2018
DOI: 10.1093/mnras/sty994
|View full text |Cite
|
Sign up to set email alerts
|

Supernova feedback in numerical simulations of galaxy formation: separating physics from numerics

Abstract: While feedback from massive stars exploding as supernovae (SNe) is thought to be one of the key ingredients regulating galaxy formation, theoretically it is still unclear how the available energy couples to the interstellar medium and how galactic scale outflows are launched. We present a novel implementation of six sub-grid SN feedback schemes in the moving-mesh code Arepo, including injections of thermal and/or kinetic energy, two parametrizations of delayed cooling feedback and a 'mechanical' feedback schem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 114 publications
(189 reference statements)
5
111
1
Order By: Relevance
“…For instance, in Hopkins et al (2018c) it is shown that the exact level of star formation is independent of the value of ε, provided that star formation is indeed feedback regulated. We have not explicitly checked this in our model and instead we have chosen a value more in line with observational determinations (see also Smith et al 2018). Also, Agertz et al (2013) report that variations of a factor of two in the normalization of the Kennicutt-Schmidt relation Kennicutt (1998) are possible when passing from ε = 0.01 to ε = 0.1.…”
Section: Star Formation Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Hopkins et al (2018c) it is shown that the exact level of star formation is independent of the value of ε, provided that star formation is indeed feedback regulated. We have not explicitly checked this in our model and instead we have chosen a value more in line with observational determinations (see also Smith et al 2018). Also, Agertz et al (2013) report that variations of a factor of two in the normalization of the Kennicutt-Schmidt relation Kennicutt (1998) are possible when passing from ε = 0.01 to ε = 0.1.…”
Section: Star Formation Implementationmentioning
confidence: 99%
“…Several schemes have been devised to account for this process (see e.g. Kimm & Cen 2014;Gatto et al 2015;Kimm et al 2015;Kim & Ostriker 2017;Rosdahl et al 2017;Hopkins et al 2018b;Smith et al 2018). In our model, we do so by boosting the momentum imparted to each gas cell i influenced by SN feedback as…”
Section: Accounting For Pdv Work In the Sedov-taylor Phasementioning
confidence: 99%
“…All simulations use the Wendland C2 smoothing kernel (Dehnen & Aly 2012) to avoid pairing instabilities and a number of 50 neighbour particles in the calculation of the smoothed hydrodynamic properties. All simulations in the NIHAO project, including the ones used here, employ a pressure floor to keep the Jeans mass of the gas resolved and suppress artificial fragmentation (see also appendix A1 of Smith et al 2018). Our implementation follows Agertz et al (2009) which is equivalent to the criteria proposed in Richings & Schaye (2016) and fulfils the Truelove et al (1997) criterion at all times.…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…Therefore, to properly simulate the effects of supernova on the gas, we inject momentum additionally to the thermal injection if the cooling radius is not resolved. This technique, usually referred to as kinetic feedback or momentum feedback, has progressively emerged as one of the best subgrid models for supernovae explosions (Hopkins et al 2014;Kimm & Cen 2014;Kim et al 2016;Agertz & Kravtsov 2016;Rosdahl et al 2017;Smith et al 2018;Hopkins et al 2018).…”
Section: Subgrid Model For Stellar Feedbackmentioning
confidence: 99%